Transport and diffusion in boundary layers of turbulent channel flow - Sanwald, Sven; Warnatz, Jürgen; Wolfrum, Jürgen (Reactive flows, diffusion and transport, 2007)
To investigate the transport and the diffusion of scalars in a turbulent channel flow, direct numerical simulations (DNS) are performed and experiments with the same geometry have been set up to examine details of the near-wall region. Transport and diffusion are observed with flow-tagging methods. In one setup the deformation of a line of tracer-molecules, placed perpendicular to the flow direction, is investigated. Furthermore the seeding and detecting of tracer-molecules into the boundary layer has been realized in two different configurations, in order to investigate species transport between the bulk flow and the boundary layer.
Der Name J. Wolfram ist falsch geschrieben, es handelt sich um J. Wolfrum
Gesehen am 12.06.2018